(3GdCdaGJ GdhGQOI aj GdbQBf GdcQje hCdbGHgGs - (3CHh GdYHGS CMeO Hf YHO GdYRjR Hf gTGe Hf ZRhGf GdagQjs
(3ChdgG (B:s
(3GdMeO ddg Ydi GdfYeGA MeOkG HdGYO hdG GfJgGA ai QLR ebQH ddMaX cKjQ eYfi ai bdjd daX s
(3BNQgG (B:s
(3aEffi HfXegG GYJfjJ hbdeG Jdbi GdPi CedjJ efgG gfG eNJUQG eSJhYHG efbMkG edjMG egPHG cedJ gPg GdCQLhRI GdeHGQcI GdLGeYI ddCdaGJ s
(3Vef eLehY s
(3CQLhRIs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B172s
Keywords: (3GddZIs